Experimental and discrete element method study on the mechanical properties of hole-fracture sandstone - Lou, Peijie; Sun, Lichen; Pan, Cheng; Ji, Penghui; Liu, Huan (Frontiers in Materials, 2025)
To explore the interaction between holes and fractures in defective white sandstone, uniaxial compression tests were conducted on samples with varying horizontal distances between holes and fractures. The technique known as Digital Image Correlation (DIC) was employed to analyze the deformation patterns, while CT scanning technology was implemented to elucidate the interior crack propagation features. Discrete Element Method (DEM) simulations were performed to investigate the micro-scale fracture evolution. The findings demonstrate that load-bearing capacity and deformation resistance decreased as the horizontal hole-fracture distance increased. The failure mode transitioned from a mixed tensile-shear failure to a more rapid tensile failure. Tensile wing fractures caused by tensile failure reinforced the merging of rock bridges. Furthermore, the trajectories of fracture propagated from the outside to the inside of the rocks progressively simplify, resulting in accelerated instability and collapse. DEM simulations indicate that the augmentation of horizontal distance between holes and fractures influenced the displacement field and the orientation of micro-fractures inside the samples. The formation of micro-fractures progressively adhered to a “clusteringexpansion-coalescence” sequence along the paths of the hole-fracture structures. The maximum strength of the samples declined in a three-phase pattern: gradual decline, steep decline, and gradual decline. These findings provide valuable insights for engineering applications, such as tunnel excavation and mining operations.